A systematic scoping review of undergraduate nursing hub-and-spoke placement models. (9th March 2023) - Cleaver, Karen; Don, Caroline; Chojnacka, Irena; Essex, Ryan; Weldon, Sharon; Markowski, Marianne
Abstract : Background: While nursing education has been forecast to continue to grow, placement capacity is now the key factor precluding growth in supply. Aims: To provide a comprehensive understanding of hub-and-spoke placements and their ability to increase placement capacity. Method: A systematic scoping review and narrative synthesis were used (Arksey and O'Malley, 2005 ). PRISMA checklist and ENTREQ reporting guidelines were followed. Findings: The search returned 418 results. After a first and second screen 11 papers were included. Results suggest that hub-and-spoke models were generally evaluated favourably by nursing students, with a range of benefits reported. However, many of the studies included in the review were small and of low quality. Conclusion: Given the exponential increase in applications to study nursing, hub-and-spoke placements appear to have the potential to better meet these increased demands, while also providing a number of benefits.